Numerical investigations and experimental measurements on the structural dynamic behaviour of quasi-periodic meta-materials. (February 2020) - Timorian, S.; Ouisse, M.; Bouhaddi, N.; De Rosa, S.; Franco, F.
Highlights: The Thue-Morse morphism sequence is capable of providing 2D quasi-periodic pattern. Predicted stop bands of infinite lattice matches the forced response of finite model. Experimental measurements validate the results obtained by finite element model. Degree of consistency between numerical & experimental results are highly predicted. FRF of the meta-structure (junction filter) reduces maximum unwanted vibration. Abstract: The periodic structures have various applications in vibroacoustic engineering fields since they introduce frequency band effects due to the periodic discontinuities in the geometrical or material configurations: this can lead to increased performances. This paper is focused on the analysis of quasi-periodic structures: instead of using strictly repeated patterns, a certain degree of irregularity is introduced. Quasi-periodic lattices are defined as assemblies of two different elements in two directions. The assembly follows a Thue-Morse Morphism sequence which results in asymmetry in both directions. Numerical studies and experimental measurements on two-dimensional periodic and quasi-periodic lattices are thus performed. First validations are carried out by comparing the quasi-periodic lattice modelled by using finite element model with a prototype manufactured by laser machine. The wave characteristics in quasi-periodic lattice introduce elements of novelty for designing wider frequency stop bands in low frequency ranges.